Hubungan Waist Hip Ratio (WHR) dan A Body Shape Index (ABSI) dengan Tekanan Darah pada Mahasiswa Kedokteran - Hasim, Edward; Vetinly, Vetinly; Astiarani, Yunisa (Fakultas Kedokteran Universitas Riau, 2024)
Prehypertension is a condition that can increase the risk of developing hypertension and lead to various diseases such as cerebrovascular disease, coronary artery disease, and chronic kidney disease. Lifestyle factors significantly influence blood pressure, with obesity being one of the key risk factors for prehypertension. Obesity can be assessed using anthropometric measurements such as Waist-Hip Ratio (WHR) and A Body Shape Index (ABSI). This study aimed to investigate the relationship between WHR and ABSI with prehypertension among male students at the School of Medicine and Health Sciences, Atma Jaya Catholic University of Indonesia. The study employed an analytic observational design with a cross-sectional approach. The respondents consisted of active male medical students from the class of 2019–2021, with data collected using random proportional-to-size sampling. Among the 74 respondents, 28.4% had normotensive blood pressure, while 71.6% exhibited elevated blood pressure. Regarding WHR, 28.4% of respondents had values indicating a risk of hypertension, and for ABSI, 25.7% of respondents had values indicating similar risks. Bivariate analysis revealed a significant relationship between WHR and ABSI with prehypertension (p = 0.024, p = 0.045). In conclusion, this study found a significant association between WHR and ABSI with prehypertension among male medical students at the School of Medicine and Health Sciences, Atma Jaya Catholic University of Indonesia.